2022
DOI: 10.14814/phy2.15382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin‐converting enzyme inhibition on cardiovascular adaptation to exercise training

Abstract: Angiotensin-converting enzyme (ACE) activity may be one determinant of adaptability to exercise training, but well-controlled studies in humans without confounding conditions are lacking. Thus, the purpose of the present study was to investigate whether ACE inhibition affects cardiovascular adaptations to exercise training in healthy humans. Healthy participants of both genders (40 ± 7 years) completed a randomized, double-blind, placebo-controlled trial. Eight weeks of exercise training combined with placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Peak oxygen uptake (VO 2peak ) and maximal power output (W max ) were determined using a modified protocol from a previous study in our research group 22 . The patients completed an incremental cycling test to exhaustion on an electronically braked cycle ergometer (Excalibur Sport, Lode, Groningen, Netherlands) with continuous measurement of VO 2 using an online gas collection system (model Cosmed, Quark b2, Milano, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Peak oxygen uptake (VO 2peak ) and maximal power output (W max ) were determined using a modified protocol from a previous study in our research group 22 . The patients completed an incremental cycling test to exhaustion on an electronically braked cycle ergometer (Excalibur Sport, Lode, Groningen, Netherlands) with continuous measurement of VO 2 using an online gas collection system (model Cosmed, Quark b2, Milano, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest that physical performance worsened in the HF-ET group, even though we did not observe any difference in trained groups regarding molecular pathways. The effects of ACEi on physical performance are contradictory, in various studies, reported as being impaired (Minami et al, 2004;Sjúrðarson et al, 2022), enhanced (Minami et al, 2007), or unchanged (Bahi et al, 2004;Carter et al, 2011). Although the mechanism behind these findings is not clear, the hypothesis supported by Minami et al (2004Minami et al ( , 2007 is that the ACEi activate the bradykinin/nitric oxide (NO) pathway by inhibiting the skeletal muscle mitochondrial respiration and impairing the higher exercise capacity acquired by training.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism behind these findings is not clear, the hypothesis supported by Minami et al (2004Minami et al ( , 2007 is that the ACEi activate the bradykinin/nitric oxide (NO) pathway by inhibiting the skeletal muscle mitochondrial respiration and impairing the higher exercise capacity acquired by training. On the other hand, beneficial mechanisms have been proposed, including improved glucose sensitivity, endothelial function, and reduced inflammation (Wang et al, 2008;Bahi et al, 2004;Sjúrðarson et al, 2022). However, no studies have examined the effects of ACEi on exercise capacity acquired by exercise training in the obesity model.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work is conflicting whether antihypertensive medication may interfere or potentiate the benefits of PA or exercise training [24][25][26][27] . Apart from the antihypertensive medication, other drugs that are commonly prescribed to hypertensive individuals such as statins (21% in our medicated hypertensives) may also have an effect on the benefits of PA 12 .…”
Section: Discussionmentioning
confidence: 99%